Removal Of 17a- Ethynylestradiol (EE2) In Aqueous Solution Using Adsorption Onto Palm Kernel Shell (PKS) And Algal Bioremediation - Lim, Yee Ling (2017)
An estrogenic compound, 17α- Ethynylestradiol (EE2) is not only proven to be present in surface water, it has also been proven to be very harmful to aquatic life even at very low concentration. In general, the aims of this research are to validate a simple high performance liquid chromatography (HPLC) method for the detection of EE2, to conduct a comprehensive study and analysis on the optimization and kinetics of EE2 adsorption onto raw palm kernel shell (PKS) and to study the degradation ability of EE2 by bacteria/algae. A HPLC with a common C18 column is validated to be able to detect EE2 using acetonitrile and deionised water at a ratio of 45:55, 1 mL/min and wavelength of 280 nm. Meanwhile, optimization runs for PKS showed a removal of more than 92% and 70%, for powder PKS and granular PKS respectively. Both the sizes of PKS follow pseudo-second order kinetic model and fitted well to the Freundlich isotherm with regression value (R2) of more than 0.98. In thermodynamics study, the standard enthalphy change (ΔH°) for powder PKS shows a positive value at 12231.56 J/mol while granular PKS shows a negative value at -3505.02 J/mol indicating an exothermic and an endothermic nature of adsorption respectively. In addition to the adsorption method of treatment, phycoremediation which is the remediation using algae, has also been performed on the aqueous solution. A microalgae species, Ankistrodesmus falcatus, has been found to be effective to remove more than 98% of EE2 at all tested concentrations of 2 μg/mL, 5 μg/mL and 10 μg/mL in just 21 days. Overall results from these two experimental runs showed the abilities of adsorption process to reduce the treatment time and the biological method that can degrade contamination due to EE2.